قصة موسى عليه السلام مع فرعون - تركي, عبد الرحمان (جامعة الوادي - University of Eloued, 2018)
تطرقت في هذا المقال إلى ما ورد في القرآن الكريم من حقائق عن قصة موسى عليه السلام مع فرعون الذي ادّعى الربوبية ، وكانت عاقبته وجنده أن أهلكهم الله تعالى وأغرقهم في اليم ، مبينا من خلال الإتيان بالحقائق زيف كثير مما ورد في التوراة المحرفة والروايات الإسرائيلية عن هذه القصة . إن النبي موسى عليه السلام من أولي العزم من الرسل ، كلّمه الله تكليما ، وهو الذي طلب رؤية الله في الدنيا ، وهو النبي الأكثر ذكرا في القرآن الكريم ، وقصته في القرآن والسنة متعددة المحطات وعديدة الموضوعات (موسى عليه السلام وفرعون حاكم مصر - موسى عليه السلام والرجل الصالح في مدين - موسى عليه السلام وبنو إسرائيل الذين أرادوا عبادة العجل الذهبي والذين طلبوا منه رؤية الله تعالى في الدنيا - موسى وأخوه هارون عليهما السلام - موسى والخضر عليهما السلام وآداب المعلم والمتعلم ... ) . Abstract: This research highlights the realties and truths cited in the Holy Coran about Moses (pbuh) with the Pharaoh, who claimed Godliness and whom Allah destroyed and drowned in the sea. Allah proved through displaying truths the falsehoods of most what was cited in the distorted Torah according to the Israeli versions of this story. Moses (pbuh) is from 'Oulou Al'azm' messengers, the most pertinent and patiently determined prophets. Allah talk to him directly, It was him who wanted to see Allah with his bare eyes in life. He was also the most highly cited Messenger in the Coran. His story in the Coran includes several phases and topics: Moses (pbuh) and the Pharaoh ruler of Egypt- Moses with the virtuous Man in Medina- Moses (pbuh) and the sons of Israel who wanted to worship the golden calf, and to see Allah in life- Moses and his brother Aaron (pbu) them – The ethics of the teacher and learner in Moses' and Alkhidr' s story (pbu) them.
دراسة تاريخية تحليلية تعتمد على بعض تفاسير القرآن الكريم وكتب قصص الأنبياء المعاصرة
مقال
Keywords: موسى عليه السلام - القرآن الكريم - السنة النبوية – فرعون عليه لعنة الله – بنو إسرائيل